Quantifying stabilizing additive hydrolysis and kinetics through principal component analysis of infrared spectra of cross-linked polyethylene pipe. (June 2022) - Grossutti, Michael; Hiles, Melanie; D'Amico, Joseph; Wareham, W. Callum; Morling, Benjamin; Graham, Scott; Dutcher, John R.
Highlights: We have used principal component analysis (PCA) of infrared (IR) microscopy data of aged PEX-a pipe to identify and track changes to stabilizing additives. We identified distinct ageing pathways for ageing PEX-a pipes in hot air and hot water. PCA of IR microscopy data provided evidence for the second-order autocatalytic hydrolysis of ester linkages in a stabilizing additive. We observed significant hydrolysis of the stabilizing additive within days of ageing PEXa pipes in hot water (85℃). Ageing of PEX-a pipe in high temperature distilled water produced IR spectral changes consistent with those measured for in-service pipe, suggesting that hot water is the most important contributing fact. Abstract: Peroxide crosslinked high-density polyethylene (PEX-a) is increasingly being used to replace traditional metal and concrete pipes in applications such as water, gas, and sewage transport. Stabilizing additives play important roles in enhancing the long-term stability of PEX-a pipes and understanding changes to these additives under in-service conditions is critical to further improvements in pipe lifetimes. We used infrared (IR) microscopy to measure spectra within the central portion of the walls of PEX-a pipe subjected to two different types of ageing: exposure to high temperature ( 85 ∘ C ) air and exposure to high temperature ( 85 ∘ C ) water. To analyze these data, we used principal component analysis (PCA) to implement an unsupervised multivariate analytical approach. This allowed us to identify distinct ageing pathways for the two types of ageing in the two-dimensional space defined by the first two principal components PC1 and PC2, which together account for 88% of the variance in the data. This representation of the data allowed us to associate each PC with different ageing processes in the pipes: changes in PC1 were due primarily to hydrolysis of stabilizing additive ester linkages, whereas changes in PC2 were due primarily to elevated temperature. The PCA showed that ageing in high temperature water produced spectral changes consistent with those measured for an in-service pipe and that water is the key component driving the changes. The results provide important information for PEX-a pipe ageing and stabilizing additive formulation design.